Impact of Ujjwala Yojana on Rural Women’s Life: Promoting Clean Fuels and Empowering Rural Women (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The smoke that rises from cooking food in the wood surrounds women with many types of diseases likes respiratory and headache. In the view of these problems of women PRADHAN MANTRI UJJWALA YOJANA (PMUY) was launched on 1st may 2016 with slogan of ‘clean fuel and better life’. The Ujjwala yojana envisages a smokeless Indian rural life. This scheme will increases the uses of LPG and will reduce health related disorders, air pollution and deforestation because around 41 of households in India are still using fossil fuel for cooking. The outline of this scheme was prepared in the form of ‘GIVE IT UP’ in 2015 itself and the financially prosperous LPG connection holders were requested by the Prime Minister to give up their subsidy. The result of which that more than 1.13 crore people gave up their subsidies, Maharashtra remained at the forefront of giving up the subsidy.According to the WHO, smoke from a stone causes the same harm as burning 400 cigarettes in an hour. According to the second report of this organization, more than 5 lakh women have to lose their lives every year due to cooking with fossil fuel in India. This scheme will encourage women empowerment and a healthy society will be created.